Laboratory manual of microbiology and biotechnology - Aneja, K. R. (Medtech, 2014)
Microbiology and biotechnology are the two important practical oriented subjects in the biology curriculum. Apart from the theoretical background, experimentation in these subjects demands special techniques and appropriate laboratory set up, especially in the field of diagnostic and molecular biology. Based on students and teachers input author's own experience of four decades of teaching and research, Laboratory manual of microbiology and biotechnology, has been designed for use by the students of microbiology, biotechnology, biological sciences, health sciences, environmental science, agriculture, pharmacy, medical laboratory technology; by workers of food processing units, beverage industries and clinical laboratories. The intent of the tool is to provide basic and recent information and in depth methodology in a simple language to help students and professionals to perform practicals with their utmost ease in quest of achieving hundred per cent success. For a beginner information no microbial diversity, various tools and techniques used to study microbes have been given